Closed flux tubes in D = 2 + 1 SU(N ) gauge theories: dynamics and effective string description - Athenodorou, A; Teper, M (Springer Verlag, 2016)
We extend our earlier calculations of the spectrum of closed flux tubes in SU(N) gauge theories in 2 + 1 dimensions, with a focus on questions raised by recent theoretical progress on the effective string action of long flux tubes and the world-sheet action for flux tubes of moderate lengths. Our new calculations in SU(4) and SU(8) provide evidence that the leading O(1/lγ) non-universal correction to the flux tube ground state energy does indeed have a power γ ≥ 7. We perform a study in SU(2), where we can traverse the length at which the Nambu-Goto ground state becomes tachyonic, to obtain an all-N view of the spectrum. Our comparison of the k = 2 flux tube excitation energies in SU(4) and SU(6) suggests that the massive world sheet excitation associated with the k = 2 binding has a scale that knows about the group and hence the theory in the bulk, and we comment on the potential implications of world sheet massive modes for the bulk spectrum. We provide a quantitative analysis of the surprising (near-)orthogonality of flux tubes carrying flux in different SU(N) representations, which implies that their screening by gluons is highly suppressed even at small N.